ENHANCING PROFESSIONAL COMPETENCIES WITH HYPERMEDIA: A STUDY OF VOCATIONAL ENGLISH TEACHER - Aditama, Madya; Winaryati, Eny; Wibisana, Mohammad Andre; Anasa, Firyal Afaf; Risqi, Saiful (ELTIN Journal, 2025)
The development of competencies is crucial for teachers in the era of Education 5.0. The advancement of technology and science requires teachers to master the concepts and use of these technologies in teaching learning process. The rapid advancements in technology and science demand that teachers in the era of Education 5.0 enhance their competencies, particularly in integrating digital tools into the teaching-learning process. This study explores the role of hypermedia in enhancing the professional competence of English teachers at SMK Negeri 1 Kandeman, with a particular focus on its potential to support self-directed learning, continuous professional development, and collaborative practices. Using a phenomenological approach, data were collected through interviews, observations, and documentation involving five English teachers. The findings reveal that hypermedia empowers teachers to adopt innovative teaching strategies and fosters growth in four key areas: pedagogical competence, professional competence, social competence, and personal development. The research highlights the need for ongoing professional development programs to help teachers effectively integrate hypermedia into their teaching practices, aligning with the goals of the Merdeka Curriculum framework. This study contributes to understanding the intersection of digital tools and teacher competence in vocational education, offering valuable insights for future educational policies and practices.